FEEDING EFFECT OF INULIN DERIVED FROM DAHLIA TUBER COMBINED WITH Lactobacillus sp. ON MEAT PROTEIN MASS OF CROSSBRED KAMPONG CHICKEN - Abdurrahman, Z. H.; Pramono, Y. B.; Suthama, N. (Diponegoro University, 2016)
The objective of the study was to determine the effects of feeding Lactobacillus species (Lactobacillus sp.) and inulin derived from dahlia tuber powder on antioxidant activity, calcium mass, and protein mass of crossbred kampong chicken meat. A total of 168 birds of 21 days old crossbred kampong chickens were randomly allocated into 6 treatments with four replications per treatment. The present experiment was assigned in a completely randomized design with 2 x 3 factorial scheme. The first factor was levels of dahlia tuber powder, namely 0.8% (A1) and 1.2% (A2), and the second factor was levels of Lactobacillus sp., namely none (B0), 1.2 mL (108 cfu/mL/B1) and 2.4 mL (108 cfu/mL/B2). The parameters measured were antioxidant activity, meat calcium and protein mass. Data were subjected to analysis of variance and followed by Duncan multiple range test (P